Blame avoidancee credit claiming : culpa e crédito no federalismo brasileiro - Ana Tereza Ribeiro Fernandes (2018)
This research intends to investigate whether the triune federalism adopted in Brazil can offer opportunities for manifestation of blame avoidance or credit claiming by actors in the executive branch of the federated entities. This research will be based on the study of the theoretical framework of federalism, on the relationship between this institution and party dynamics, and on theories that seek to identify patterns of attribution of responsibility in decentralized power settings. The model adopted in Brazil is particularly interesting for this study, due to its cooperative and coordinated characteristics and the existence of different standards of competences established by sectorial public policies. In this context, the case of the Mariana disaster of 2015 and the RIO 2016 Olympic Games were chosen as case study objects. Based on them, it is possible to affirm that the attribution of blameand the claim of credit in the scope of federalism is a complex phenomenon that must be addressed considering both behaviors. In addition, the blame avoidance strategies systematized in the literature can be extended to the understanding of credit claiming, and there is no prescription that determines a priori how they should be applied, which depends on the concrete case. Finally, it can be observed that the existence of multiple actors in competition for a favorable reputation towardthe electorate canbe related to the behaviors studied, as well as to the way in which competencies are distributed in the federative environment.